Atividade antimicrobiana, antibiofilme, cito e genotóxica do S- (3,4-diclorobenzil) isotioureia (A22) - Bonez, Pauline Cordenonsi (2017)
Biofilm formation causes great public health concern due to the low response to antimicrobial treatments and the colonization of surfaces such as prostheses and catheters. Pathogenic microorganisms such as Pseudomonas aeruginosa are able to form biofilms in medical devices and living tissues, can cause severe chronic infections in humans. Thus, it is important to search effective alternatives against the formation of biofilms. A22 inhibits MreB protein from the bacterial cytoskeleton altering the microbial cells shape, which can affect many properties, including motility and biofilm formation. In this context, this work aimed to evaluate, for the first time, the antibiofilm action of A22 on P. aeruginosa, as well as their potencial cyto and genotoxic effects. The antibacterial activity of A22 was evaluated by conventional methods on standard strains and 28 multiresistant clinical isolates of P. aeruginosa. The cyto and genotoxicity tests were performed by MTT test and Comet assay, respectively. The adhesion capacity of clinical isolates and standard strain was measured in polyestyrebe plates. Essential factors to the biofilm physiology of P. aeruginosa, such as swimming, swarming ant twitching motility, as well as adhesion to HeLa cells and adhesion to High Density Polyethylene (HDPE) were evaluated in the presence and absence of A22. Atomic Force Microscopy (AFM) was used to visualize adhesion on HDPE substrate. This study confirmed the excellent antimicrobial activity of A22, especially in relation to multiresistant isolates. Likewise, A22 showed no cytotoxic effects on human Peripheral Blood Mononuclear Cells (PBMCs) at all exposure times, with exception of concentration of the 32μg/mL, and did not demonstrate genotoxic effects on the cells after 24 and 48 hours. In addition, the results showed a high adhesion pattern in 14 multiresistant clinical isolates, with inhibiting the adhesion of 9 of these microorganisms. A22 was able to decrease adhesion and biofilm formation of the P. aeruginosa PAO1 on polyestyrene plates, HeLa cells and HDPE. Moreover, the swarming and twitching motilities were significantly decreased by A22 in subinhibitory concentrations. The impact and scientific contribution of this work are based on the discovery of a potencial new therapeutic possibility against infections associated with biofilms of P. aeruginosa. The A22 presents as an useful and promising tool to decrease microbial adhesion in both living and inert surfaces, given its low toxic effects. However, this thesis results stimulate the deepening in methodologies that aim the insertion of A22 as a new antibacterial or coating agent on medical materials.